PERENCANAAN KAPASITAS PRODUKSI DENGAN PENDEKATAN BIAYA MARJINAL PADA PABRIK TAHU â€œSBRâ€ BENGKULU - Afifi Bachtiar (Creative Research Management Journal, 2018)
Production capacity planning with a marginal cost approach and marginal sales proceeds to get the maximum profit at Bengkulu's "SBR" factory. This study aims to find out what the marginal production capacity planning will be produced with the marginal cost approach at Bengkulu's "SBR" plant. This research method is to establish a direct relationship with the tuhu factory "SBR" Bengkulu. The method of analysis is qualitative and quantitative analysis. The variables analyzed in this study are capacity planning and marginal cost. The calculation results are known that the factory knows "SBR" produces marginal production of 120 packs, with the minimum marginal cost of Rp 156.25 occurring in the third quarter of 2012. When compared with production knew that in the fourth quarter of 2012, the factory knew that Bengkulu's "SBR" had a marginal production of 80 packs with a marginal cost of Rp. 2000, so it would be more profitable when marginal production was 120 packs. These results can be concluded that production capacity planning with a marginal cost approach will benefit the factory knowing "SBR" Bengkulu.